2022
DOI: 10.3390/w14101568
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Conditions along Tuna Larval Dispersion: Insights on the Spawning Habitat and Impact on Their Development Stages

Abstract: Estimated larval backward trajectories of three Tuna species, namely, Atlantic Bluefin Tuna (Thunnus thynnus, Linnaeus, 1758), Bullet Tuna (Auxis Rochei, Risso, 1801) and Albacore Tuna (Thunnus alalunga, Bonnaterre, 1788) in the central Mediterranean Sea, were used to characterize their spawning habitats, and to assess the impact of changes due to the major environmental parameters (i.e., sea surface temperature and chlorophyll-a concentration) on larval development during their advection by surface currents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 72 publications
3
4
0
Order By: Relevance
“…The observed pattern is further supported by the similarity between the response plots of the two explanatory factors Longitude and Salinity in Figures 4A, B, as it known that surface salinity locally presents a west-east increasing gradient that is induced by the motion of Atlantic Modified Water toward the Eastern Mediterranean basin (Robinson et al, 1999;Garcıá Lafuente et al, 2002). Therefore, the importance of concentration and retention processes locally induced by oceanographic features is confirmed by the present study (Figure 3A), not only in support of larval growth and survival, and related enhanced probability of recruitment success for many fish species as already shown by previous studies in the SoS (Torri et al, 2018;Patti et al, 2020;Russo et al, 2021;Torri et al, 2021;Russo et al, 2022;Cuttitta et al, 2022), but also more in general for sustaining high biodiversity levels (Figure 3B). Actually, frontal structures are generally responsible for plankton aggregation, so supporting the increase in feeding opportunities for fish larvae and inducing favorable conditions for their survival, as already observed in many other marine environments including the Mediterranean Sea (Bakun, 2006;Alemany et al, 2010;Avendaño-Ibarra et al, 2013;Erisman et al, 2017;Acha et al, 2018;Sato et al, 2018;Torri et al, 2018;Patti et al, 2020;Russo et al, 2021;Torri et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…The observed pattern is further supported by the similarity between the response plots of the two explanatory factors Longitude and Salinity in Figures 4A, B, as it known that surface salinity locally presents a west-east increasing gradient that is induced by the motion of Atlantic Modified Water toward the Eastern Mediterranean basin (Robinson et al, 1999;Garcıá Lafuente et al, 2002). Therefore, the importance of concentration and retention processes locally induced by oceanographic features is confirmed by the present study (Figure 3A), not only in support of larval growth and survival, and related enhanced probability of recruitment success for many fish species as already shown by previous studies in the SoS (Torri et al, 2018;Patti et al, 2020;Russo et al, 2021;Torri et al, 2021;Russo et al, 2022;Cuttitta et al, 2022), but also more in general for sustaining high biodiversity levels (Figure 3B). Actually, frontal structures are generally responsible for plankton aggregation, so supporting the increase in feeding opportunities for fish larvae and inducing favorable conditions for their survival, as already observed in many other marine environments including the Mediterranean Sea (Bakun, 2006;Alemany et al, 2010;Avendaño-Ibarra et al, 2013;Erisman et al, 2017;Acha et al, 2018;Sato et al, 2018;Torri et al, 2018;Patti et al, 2020;Russo et al, 2021;Torri et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…This emphasizes the role of oceanic conditions in influencing the presence and abundance of these species. Interestingly, similar results have been found in studies focused on larval dispersion of other species occurring in the same area (Torri et al, 2021;Russo et al, 2022), highlighting the importance of the hydrodynamics in a key area for the thermohaline circulation of the Mediterranean Sea, where exchange of water masses between western and eastern basins take place (Placenti et al, 2022). Furthermore, the analysis showed that temperature plays a significant role in explaining the abundance of Sardinella aurita.…”
Section: Discussionsupporting
confidence: 80%
“…This finding evidenced a southward dispersion process that appears additional to the one described in most of the literature existing in this study area. Here, many authors identify an advection originating from the western zones of the Strait of Sicily and linked to the south-eastward flow of the fresher surface Atlantic Ionian Stream (AIS), which here dominates the superficial hydrodynamics (Robinson et al, 1999) and plays a key role in transporting planktonic fish stages to waters off CP (Garcıá Lafuente et al, 2002;Falcini et al, 2015;Cuttitta et al, 2018;Torri et al, 2018;Patti et al, 2020;Torri et al, 2021;Russo et al, 2022). In this context, CP has been described as an important retention zone due to the presence of a cyclonic structure and a saline front, which create favourable conditions for the recruitment of fish species in the area.…”
Section: Discussionmentioning
confidence: 99%